2018
DOI: 10.1093/ecco-jcc/jjy147
|View full text |Cite
|
Sign up to set email alerts
|

Lower Abundance and Impaired Function of CD71+ Erythroid Cells in Inflammatory Bowel Disease Patients During Pregnancy

Abstract: Background and Aims: CD71 + erythroid cells are enriched during pregnancy with immuno suppressive properties. We investigated the frequency and functionality of CD71 + erythroid cells in peripheral blood, cord blood, and placenta of inflammatory bowel disease [IBD] patients versus healthy controls [HCs]. We aimed to determine their role in IBD pathogenesis during pregnancy. Methods: Peripheral blood was collected at preconception, the first, second and third trimesters, and postpartum. Cord blood and placental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 47 publications
10
75
0
Order By: Relevance
“…More importantly, we observed that CECs release mitochondrial ROS, which its function can be abrogated by ROS-scavenger Apocynin but not by N-acetyl cysteine. Interestingly, we observed that CECs when obtained from the cord blood of mothers with IBD did not enhance HIV-1 infection in autologous CD4 + T cells because of their impaired ROS production ability (10).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…More importantly, we observed that CECs release mitochondrial ROS, which its function can be abrogated by ROS-scavenger Apocynin but not by N-acetyl cysteine. Interestingly, we observed that CECs when obtained from the cord blood of mothers with IBD did not enhance HIV-1 infection in autologous CD4 + T cells because of their impaired ROS production ability (10).…”
Section: Discussionmentioning
confidence: 85%
“…Despite these reports, the interaction of erythroid precursors with HIV-1 has never been investigated and has remained a mystery. We have recently reported abundance of erythroid precursors (CECs) in the cord blood, placental tissues and the peripheral blood of pregnant mothers (10,15,34). We further indicated that CECs possess a wide range of immunological properties (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations